A highly selective and sensitive fluorescent probe based on the chromone fluorophore for imaging hydrogen sulfide in living cells. (8th January 2020) - Hou, Fei; Zhu, Li; Zhang, Hongyi; Qiao, Zhen; Wei, Ningning; Zhang, Yanru
Abstract : A fluorescent probe that was designed based on the 6-amino chromone fluorophore for detecting H2 S can distinguish H2 S from Cys/GSH under acidic conditions. Abstract : Hydrogen sulfide (H2 S) is an important biological molecule that plays a crucial role in physiological and pathological processes, and it is closely related with several diseases including cancer, diabetes and Alzheimer's disease. Therefore, detecting the level of H2 S in biological systems is significant to understand and treat these diseases. Although many fluorescent probes have been developed to monitor different H2 S in biosystems, there is still a lack of fluorescent probes that can detect H2 S in acidic environments for understanding its roles in cancer tissues. In this work, we developed a novel fluorescent probe for detection of H2 S based on the chromone fluorophore. This probe responds well to H2 S under acidic conditions, demonstrates high selectivity, sensitivity and a large Stokes shift of 150 nm, and can be applied in imaging of H2 S in living cells.